2017
DOI: 10.31072/rcf.v8i2.569
|View full text |Cite
|
Sign up to set email alerts
|

Adubação e nutrição da batata-doce: uma revisão

Abstract: A batata-doce é uma cultura importante para alimentação da população, sendo rica em proteínas, fibras, nutrientes como potássio (K), fósforo (P), cálcio (Ca), magnésio (Mg), ferro (Fe), manganês (Mn), cobre (Cu), e compostos bioativos. É cultivada em geral por pequenos produtores. No Brasil, a produtividade obtida é muito inferior ao potencial produtivo da cultura. A nutrição e adubação da cultura da batata-doce é um tema bastante complexo e contraditório. O objetivo deste trabalho foi analisar os trabalhos ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…In addition, the crop is able to exploit the soil well in a way that expresses high productivity even in soils without high fertility, being dispensable in liming. However, the studies found in the literature related to sweet potato fertilization show contradictory results, and local studies are essential to define the ideal fertilizer dose (Oliveira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the crop is able to exploit the soil well in a way that expresses high productivity even in soils without high fertility, being dispensable in liming. However, the studies found in the literature related to sweet potato fertilization show contradictory results, and local studies are essential to define the ideal fertilizer dose (Oliveira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The harvest and evaluation of the experiment were carried out in March 2020. The harvest was carried out 180 days after planting since, in tropical soils the later harvest results in higher yields when compared to the usual four to five months after planting (Oliveira et al, 2017). The following parameters were evaluated: total productivity (TP) and commercial productivity (CP) in t ha -1 , followed by economic analysis of fertilization; number of total tuberous roots (NTR) and number of commercial tuberous roots (NCR) per plant; harvest index (HI) in percentage; of each tuberous root, the individual fresh mass (IFM) was expressed in g, length (L) and diameter (D) in cm.…”
Section: Evaluated Parametersmentioning
confidence: 99%
“…In Brazil, crop fertilization with bovine manure has stood out due to its benefits in both vegetable yield and quality, highlighting its potential use to enhance yield of tuberous crops, especially those grown in nutrient-poor soils (Oliveira et al, 2017), as observed for the yam crop (Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Its root tubers are consumed and are the main commercial part of this plant. Sweet potato has high yield potential and wide phenotypic and genotypic variability, but the average yield in Brazil is low: approximately 12 Mg ha -1 (Oliveira et al 2017). This is because most sweet potato crops are grown from local non-selected varieties and use a low level of technology, which results in yields below crop potential.…”
Section: Introductionmentioning
confidence: 99%